Dogs in passenger vehicles – crash safety evaluation of travel crates. Issue 3 (4th May 2018) - Ivarsson, B. Johan; Davidsson, Johan
ABSTRACT: Methods for evaluating the crash safety of travel crates for transportation of dogs in the vehicle cargo space have previously been proposed. This study aims to (1) explore how two crate designs, a plastic crate and a metal crate, previously evaluated according to the Center for Pet Safety (CPS) method that only accounts for frontal impact, perform when evaluated according to the Safe Pet Crate Test (SPCT) that accounts for multiple crash modes, and (2) evaluate if the use of standard vehicle cargo hooks for securing the crate and a standard vehicle seatback, as opposed to the 'strength-rated' anchor points and rigid seatback structure specified for the CPS method, yields results consistent with published CPS method test results. Frontal and rear-end impact sled tests and drop tests were conducted. The results indicate that the metal crate, which did not comply with the CPS method, offers safety benefits over the plastic crate which complied with the CPS method. The results further indicate that the limited strength of standard vehicle cargo hooks and limited strength and stiffness of vehicle seatbacks may both affect the frontal crash response of crates initially positioned away from the seatback and therefore must be accounted for.